Diagnosis and treatment of acute venous thrombosis - González Vales, Horacio; Danza, Rómulo (Cirugía del Uruguay, 2021)
The authors present an updated summary of the venous physiopathology of acute thrombosis in the limbs ann insist, for the purpose of establishing an early diagnosis, in the signs of pain induced by palpation of the fenous trunk. With respect to tne treatment they refer mainly to the technique of thrombectomy with preservation of the venous light. They peesent a series of 49 cases which were subject to different treatments, with 20 cases of thrombectomy; with this last therapeutical method they have obtained 80 % success.